T1 Relaxation Time of Achilles Tendon at 3 Tesla with Special Reference to Relevant Clinical Score: A Preliminary Study - Tbini, Zeineb; Mars, Mokhtar; Bouaziz, Mouna (Current medical imaging reviews, 2020)
The purpose of this study was to investigate T1 relaxation time of the human Achilles tendon, to test its short-term repeatability as well as the minimal detectable change, and to assess the extent that correlate with clinical symptoms. Twenty asymptomatic volunteers and eighteen patients with clinically and sonographically confirmed tendinopathy were scanned for ankle using a 3 Tesla (T) MR scanner. T1 maps were calculated from a variable flip angle gradient echo Ultra-short echo time sequence (VFA-GE UTE) and inversion recovery spin echo sequence (IR-SE) using a self-developed matlab algorithm in three regions of interest of Achilles Tendon (AT). Signal to Noise Ratio (SNR) between the two sequences was evaluated. INTRA-class Correlation Coefficient (ICC), Coefficient of Variation (CV) and the Least Significant Change (LSC) were calculated, to test short-term repeatability of T1. Subjects were assessed by the VISA-A clinical score. P values less than 0.005 were considered statistically significant. Mean T1 values were 427.09 ± 53.37 ms and 528.70 ± 103.50 ms using IR-SE sequence and 575.43 ± 110.60 ms and 875.81 ± 425.77 ms with VFA-GE UTE sequence in the whole AT for volunteers and patients, respectively. T1 values showed a significant difference between volunteers and patients (P=0.001). Regional variation of T1 in healthy and tendinopathic AT were greater for VFA-GE UTE sequence than for IR-SE sequence. VFA-GE UTE sequence showed clearly higher SNR compared to IR-SE sequence. Short-term repeatability of T1 values for volunteers showed an LSC of 22% and 14% for IR-SE sequence and VFA-GE UTE sequence, respectively. For patients, LSC was 14% and 5% for IR-SE sequence and VFA-GE UTE sequence, respectively. There was no correlation between T1 and VISA-A clinical score (p>0.005). VFA-GE UTE sequence used for T1 mapping calculation demonstrated short acquisition time and clearly high SNR. Results revealed that T1 relaxation time can be used as a biomarker to differentiate between healthy and pathologic Achilles tendon. However, T1 showed no correlation with the VISA-A clinical score.